2011
DOI: 10.1186/1472-6882-11-83
|View full text |Cite
|
Sign up to set email alerts
|

Tactile massage and hypnosis as a health promotion for nurses in emergency care-a qualitative study

Abstract: BackgroundThis study explores nursing personnel's experiences and perceptions of receiving tactile massage and hypnosis during a personnel health promotion project. Nursing in a short term emergency ward environment can be emotionally and physically exhausting due to the stressful work environment and the high dependency patient care. A health promotion project integrating tactile massage and hypnosis with conventional physical activities was therefore introduced for nursing personnel working in this setting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A combination of massage, relaxing music and aromatherapy was also shown to be effective in reducing anxiety for emergency nurses [12]. Similarly, a combination of tactile massage and hypnosis helped reduce the stress and pain levels, and increase the work ability, of short-term emergency ward nurses [13]. Finally, a pilot study, involving healthcare workers at a LTC facility for adults with severe disabilities, found that a once-weekly 20-min massage initially decreased pain severity, and showed some evidence of improving job satisfaction and morale [14].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of massage, relaxing music and aromatherapy was also shown to be effective in reducing anxiety for emergency nurses [12]. Similarly, a combination of tactile massage and hypnosis helped reduce the stress and pain levels, and increase the work ability, of short-term emergency ward nurses [13]. Finally, a pilot study, involving healthcare workers at a LTC facility for adults with severe disabilities, found that a once-weekly 20-min massage initially decreased pain severity, and showed some evidence of improving job satisfaction and morale [14].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown a lack of HPBs in the areas of physical activity, stress management, and healthy diet among nurses (Airosa et al, 2011;Dam et al, 2008;Thacker, Stavarski, Brancato, Flay, & Greenawald, 2016;Lee, 2013;Lee & Shin, 2014;McElligott, Siemers, Thomas, & Kohn, 2009;Mostafaei Najaf-Abadi & Rezaei, 2017;Ratner & Sawatzky, 2009;Liu, 2012 andTucker, Harris, Pipe, &Stevens, 2010). Several studies have reported that more than half of the nurses were overweight or obese and had no physical activity standards (ANA, 2017;Poghosyan, Clarke, Finlayson, & Aiken, 2010;Tucker et al, 2010;Zhao, Bogossian, & Turner, 2012).…”
mentioning
confidence: 99%
“…For nurses, daily work in a short-term emergency ward can be exhausting due to its technical and stressful environment with high demands (Airosa et al, 2011;Yang et al, 2001). For nurses, daily work in a short-term emergency ward can be exhausting due to its technical and stressful environment with high demands (Airosa et al, 2011;Yang et al, 2001).…”
Section: Patients' Experience Of Massage In Acute or Intensive Carementioning
confidence: 99%